KORUPSI DI KALANGAN PENEGAK HUKUM DAN SELEKSI HAKIM SEBUAH PENDEKATAN SEJARAH - Chatamarrasjid Ais (Lembaga Penelitian Universitas YARSI, 2019)
Corruption has been in existence since the human history began. Such practice is rife notonly among commoners in the society but also among law enforcers. Some measures havebeen taken to prevent corruption from occurring among law enforcers; one of which istight selection when recruiting in-service judges or justices and other law enforcers.Indonesian Judicial Commission which is in charge of this selection process proposes andsubmits three times the number of expected justices to the House of Representatives whowill then—from the names given—choose the appointed supreme court justice. It isassumed that the appointed officer is the one who possesses solid integrity, is capable ofpreventing corruption practices, and has the courage to give punishments to theperpetrators of corruption. This research is normative in nature, applying literature-studymethod, with history and statute approach. History has shown evident differences betweenin-service judge selection process in the past and the one of today. There is cleardistinction between these two selection processes in terms of the candidates’ origin andselection requirements. Prabu Hayam Wuruk has apparently laid the basis of supremecourt justice selection process to generate justice with high integrity. According to itsvision and mission, Judicial Commission is expected to perform well by—in this particularmatter—recruiting quality justices.